2015
DOI: 10.1071/cp14063
|View full text |Cite
|
Sign up to set email alerts
|

Potential legume alternatives to fallow and wheat monoculture for Mediterranean environments

Abstract: Growing populations and intensification of land-use in West Asia and North Africa (WANA) are prompting a need for viable alternatives to fallow and cereal mono-cropping systems common in dry areas of this region. The sustainability and economic viability of such rotations can only be assessed accurately by using long-term trials. A two-course rotation experiment was established in 1986 in north-eastern Syria, comparing yields and profitability of wheat (Triticum aestivum L.) when grown after wheat, fallow, a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The yield benefits of crop rotation, especially of cereals with legumes, have been accepted in practice by farmers in many dryland systems for a very long time, and recently reaffirmed from long-term experiments in northern Syria (Christiansen et al 2015) and Western Australia (French et al 2015). However, published reports do not always support the claim that soil and yield improvements come from the retention of crop residues (Scott et al 2010).…”
Section: Relative Contributions-management and Breedingmentioning
confidence: 72%
“…The yield benefits of crop rotation, especially of cereals with legumes, have been accepted in practice by farmers in many dryland systems for a very long time, and recently reaffirmed from long-term experiments in northern Syria (Christiansen et al 2015) and Western Australia (French et al 2015). However, published reports do not always support the claim that soil and yield improvements come from the retention of crop residues (Scott et al 2010).…”
Section: Relative Contributions-management and Breedingmentioning
confidence: 72%
“…The increased available N in the pulse systems reflects the process by which the plants fix atmospheric N 2 through symbiosis with soil Rhizobium and the decomposition of the N-rich crop residues, a biological process that is environmentally friendly 22,43 . By contrast, the increased soil N with summerfallow systems is mainly through 'mining' the soil and accelerating the depletion of the soil organic matter 23 , which is a soil-degrading and environmentally detrimental approach 44 . One of the major goals of farming is to increase the crop yield per unit of input 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of pulse crops in farming systems can enhance soil available N 21 due to the ability of pulse plants to fix atmospheric N 2 through symbiosis with Rhizobium 22 . In many areas of Mediterranean countries, the use of pulses to enhance soil N has been practiced for decades, and the advantages have been widely demonstrated 23,24 . However, it is not known whether diversifying summerfallow systems with pulses is effective and productive in the northern latitude areas where water is scarce and the growing season is short (95 to 125 days) 25 .…”
mentioning
confidence: 99%
“…A study of ten growing seasons in north-eastern Syria showed that the inclusion of pulses either as grain crops or hay in the rotation boosted profits considerably (Christiansen et al 2015). Replacing summerfallow with common vetch (Vicia sativa L.) for hay production increased the average gross margin by US$126 ha −1 year −1 , and growing vetch for hay in rotation with wheat produced greater profit than continuous wheat, by $254 ha −1 year −1 .…”
Section: Case Study-reducing Summerfallow Frequencies Lowers the Carbmentioning
confidence: 99%